Non-Coding RNAs as Novel Regulators of Neuroinflammation in Alzheimer’s Disease - Liu, Yuqing; Cheng, Xin; Li, Hongli; Hui, Shan; Zhang, Zheyu; Xiao, Yang; Peng, Weijun (Frontiers in Immunology, 2022)
Alzheimer’s disease (AD) is one of the most common causes of dementia. Although significant breakthroughs have been made in understanding the progression and pathogenesis of AD, it remains a worldwide problem and a significant public health burden. Thus, more efficient diagnostic and therapeutic strategies are urgently required. The latest research studies have revealed that neuroinflammation is crucial in the pathogenesis of AD. Non-coding RNAs (ncRNAs), including long noncoding RNAs (lncRNAs), microRNAs (miRNAs), circular RNAs (circRNAs), PIWI-interacting RNAs (piRNAs), and transfer RNA-derived small RNAs (tsRNAs), have been strongly associated with AD-induced neuroinflammation. Furthermore, several ongoing pre-clinical studies are currently investigating ncRNA as disease biomarkers and therapeutic interventions to provide new perspectives for AD diagnosis and treatment. In this review, the role of different types of ncRNAs in neuroinflammation during AD are summarized in order to improve our understanding of AD etiology and aid in the translation of basic research into clinical practice.